Public satisfaction with the Ethiopian healthcare system: a mixed methods approach - Getahun, Genanew Kassie; Demissie, Bemnet Dires; Baraki, Semere Gebremariam (Frontiers in Public Health, 2024)
Introduction The satisfaction of the public with the healthcare system of Ethiopia is a crucial but unanswered question. This is an essential issue since recent trends indicate that the demographic and epidemiological makeup of the population is changing. Therefore, the aim of this study was to assess the overall satisfaction of the public with the Ethiopian healthcare system in Addis Ababa, Ethiopia, in 2022. Methods A community-based convergent parallel mixed methods study was conducted. Bivariable and multivariable logistic regression analyses were used to determine the factors associated with public satisfaction. A 95% confidence interval along with a p < 0.05 was deemed sufficient to declare a significant association. For the qualitative component, we used thematic analysis. Results The vast majority, 77.2% (95% CI: 76.18–78.22%), of respondents were dissatisfied with the existing healthcare system. Moreover, Community-Based Health Insurance (CBHI) enrollment (2.35; 95% CI: 1.32–4.19), poor linkage to social capital (0.46; 95% CI: 0.25–0.83), poor access to healthcare services (0.39; 95% CI: 0.21–0.76), and absence of satisfactory responses to complaints (0.11; 95% CI: 0.04–0.27) were significantly associated with public dissatisfaction. Conclusion Public satisfaction with the Ethiopian healthcare system is notably low and is affected by various factors, including enrollment in the CBHI, linkage to social capital, accessibility to healthcare, and satisfactory response to issues. Therefore, the Ethiopian government should focus on expanding CBHI coverage, improving access to healthcare services, and developing an immediate compliant solution strategy.